Microwave‐Assisted Solid‐Phase Synthesis of a 1, 2‐Disubstituted Benzimidazole Library by Using a Phosphonium Linker. (21st May 2013) - Ríos, Natalia; Chavarría, Cecilia; Gil, Carmen; Porcal, Williams
Abstract : Abstract : An efficient and rapid microwave‐assisted solid‐phase method for the synthesis of 5‐methyl‐1, 2‐disubstituted benzimidazoles derivatives has been developed. The phosphonium linker, obtained by reaction between polymer‐supported triphenylphosphine and 4‐fluoro‐3‐nitrobenzyl iodide, underwent aromatic substitution with primary amines, followed by one‐pot reaction with aldehydes in the presence of SnCl2 ·2H2 O, yielded the benzimidazole system under microwave irradiation. The final products were released from the resin with NaOH under microwave irradiation and were obtained in high purity and good overall yield.